Diversity in Education and Its Social Implications: Predictors of Diversity Competence of the Future Teachers - Andronache, Daniel; Stănescu, Mirona-Horiana (Social Welfare: Interdisciplinary Approach, 2024)
This study explores the factors influencing the development of diversity competence in future primary and preschool teachers, focusing on age, religiosity, background, and sexual orientation. Diversity competence refers to the ability to interact effectively with diverse groups across various dimensions, such as culture, gender, religion, and socioeconomic status, allowing educators to create inclusive classroom environments that respect and value each student’s unique background. Using the DiKo rating scale, data were collected from 170 student teachers at Babeș-Bolyai University. The analysis employed Pearson correlation and regression models to assess the relationship between these demographic factors and diversity competence. The results indicate that religiosity and age have a significant, though modest, influence on diversity competence, with intrinsic religiosity linked to greater openness to diversity. Conversely, sexual orientation and background were found to have no significant impact on diversity competence. These findings have important implications for teacher education programs, particularly the need to promote empathy, self-reflection, and critical engagement with diverse groups. The study also highlights the importance of future research to further investigate the influence of sexual orientation and background on diversity competence, considering the limitations of the current sample size.